PENDAMPINGAN PENGUATAN KELEMBAGAAN KOPERASI AS-SAKINAH DALAM RANGKA KONVERSI MENJADI KOPERASI SYARIAH - Mahdi , Fadilla Muhammad; Salama, Sri Cahyaning Umi (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2022)
Purpose of the study: The purpose of this activity is to assist the management of the Malang City As-Sakinah Cooperative in converting it into a sharia cooperative through institutional assistance. The conversion to a sharia cooperative was carried out because the As-Sakinah Cooperative, which is under Islamic organization, Muhammadiyah, Malang City, wants to practice Islam as a whole, including in the economic sector. Methodology: The method used in carrying out this activity is a Focus Group Discussion (FGD) by analyzing the cooperative’s statutes and bylaws before and after conversion, then evaluating the results of the activity. Main Findings: The statutes and bylaws of the sharia version are used as material for consideration by the management of the as-sakinah cooperative. Applications of this study: This service is useful for the management of the As-Sakinah Cooperative, PDM Kota Malang, which will convert it into a sharia cooperative Novelty/Originality of this study: The As-Sakinah Cooperative can immediately convert into a sharia cooperative.